2021
DOI: 10.1055/s-0041-1728728
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factors Affecting Enuresis in 6- to 12-Year-Old Children Referred to the Pediatric Nephrology Clinic

Abstract: Enuresis is one of the most common disorders in children, and if left untreated can cause anxiety, low self-esteem, and family problems. The aim of this study was to investigate the factors associated with enuresis to provide recommendations for more efficient prevention and treatment. A cross-sectional study was performed on children aged 6 to 12 years with enuresis, referred to the pediatric clinic between April 2017 and April 2018. Children were divided into two groups: monosymptomatic enuresis and healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Selection of eligible papers were performed according to the PRISMA‐ScR document, with two independent authors for screening, full text assessment and inclusion (see Figure 1 for PRISMA 2020 selection flow diagram). Seventy‐six papers 1,10,30–103 were included. Eligible papers are summarized in Table 1, and information about candidate genes are summarized in Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selection of eligible papers were performed according to the PRISMA‐ScR document, with two independent authors for screening, full text assessment and inclusion (see Figure 1 for PRISMA 2020 selection flow diagram). Seventy‐six papers 1,10,30–103 were included. Eligible papers are summarized in Table 1, and information about candidate genes are summarized in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…The first studies to imply a familial risk in incontinence were epidemiological studies. Regarding NE, findings from the included studies 1,10,31,34,35,44,47,55,70,72,75,79,81,83,95,96 (see Table 1) suggest that NE have a genetic risk component, as the prevalence of NE in family members of enuretic children is high and varies between 15% and 76% in fathers, 14.5 in 76% in mothers, and 6%-38% in siblings. Interestingly, fathers seem to have been affected more often than mothers in most studies.…”
Section: Family and Epidemiological Studiesmentioning
confidence: 99%
“…Another study on 140 children demonstrated that family history was positive in 57.2% of children with enuresis, while this was positive in 28.6% of children without enuresis (19). In addition to positive family history, parents' educational level, birth order, family economic status, the number of siblings and family members, a history of previous urinary tract infections, and constipation are associated with enuresis (19,20).…”
Section: Etiology and Epidemiologymentioning
confidence: 99%